Efficient gene deletion of Integrin alpha 4 in primary mouse CD4 T cells using CRISPR RNA pair-mediated fragmentation - Wi, Taeuk; Choi, Yurim; Kim, Jungsun; Choi, Youn Soo; Pipkin, Matthew E.; Choi, Jinyong (Frontiers in Immunology, 2024)
The functional specialization of CD4 T lymphocytes into various subtypes, including TH1 and TFH cells, is crucial for effective immune responses. TFH cells facilitate B cell differentiation within germinal centers, while TH1 cells are vital for cell-mediated immunity against intracellular pathogens. Integrin α4, a cell surface adhesion molecule, plays significant roles in cell migration and co-stimulatory signaling. In this study, we investigated the role of Integrin α4 in regulating TFH and TH1 cell populations during acute viral infection using CRISPR-Cas9 gene editing. To effectively delete the Itga4 in primary mouse CD4 T cells, we selected various combinations of crRNAs and generated ribonucleoprotein complexes with fluorochrome-conjugated tracrRNAs and Cas9 proteins. These crRNA pairs enhanced gene deletion by generating deletions in the gene. By analyzing the effects of Itga4 deficiency on TFH and TH1 cell differentiation during acute LCMV infection, we found that optimized crRNA pairs significantly increased the TH1 cell population. Our results highlight the importance of selecting and combining appropriate crRNAs for effective CRISPR-Cas9 gene editing in primary CD4 T cells. Additionally, our study demonstrates the role of Integrin α4 in regulating the differentiation of CD4 T cells, suggesting the potential molecular mechanisms driving T cell subset differentiation through integrin targeting.